Selective host-guest interaction of single-walled carbon nanotubes with functionalised fullerenes. - Britz, D; Khlobystov, A; Wang, J; O'Neil, A; Poliakoff, M; Ardavan, A; Briggs, G (2004)
Exohedrally functionalised fullerenes have been inserted in single-walled carbon nanotubes (SWNTs) with the aid of supercritical carbon dioxide to form peapods; C(61)(COOEt)(2) are encapsulated in SWNTs in high yield, whereas C(61)(COOH)(2) aggregate via hydrogen bonding to form a supramolecular complex, which sterically hinders encapsulation and causes it to adhere to the exterior surface of the SWNTs.